LoRaWAN Reliability Improvement Using Calibration of RF Planning and Redundancy: Field Results for Din Flood Alarm System - Mafra Jr, Johnny J; Carneiro Ribeiro Bueno Martins, Diogo (Street Art & Urban Creativity, 2025)
Brazil reached an all-time high of 118 dams in emergency in 2023, which warranted the development of an alarm system. Since LoRaWAN lacks reliability, mainly regarding downlink messages, this work presents a solution to take the availability to the highest levels. Alarms were 100% delivered within 5 minutes and FUOTA transmitted a firmware split into thousands of fragments reliably. It is also presented an approach to calibrate the RF simulation to make it fit better with the measurements. This took the availability from 77% to 91%. For SNR above -10 dB the availability is as good as 95%.